2014
DOI: 10.1177/239700221402800103
|View full text |Cite
|
Sign up to set email alerts
|

Is Transformational Leadership Healthy for Employees? A Multilevel Analysis in 16 Nations

Abstract: Is transformational leadership healthy for employees? A multilevel analysis in 16 nations ** This study examines the potential health promoting and hampering effects of transformational, contingent reward and laissez-faire leadership across 16 countries with a multi-source dataset comprising 93,576 subordinates in 11,177 teams of a large international company. We analyze how leadership climate strength, defined as the shared perceptions of employees concerning their supervisor's leadership behavior, affects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 57 publications
3
75
0
4
Order By: Relevance
“…Lastly, as research that examined TFL across multiple countries found that cultural dimensions influence its effects (e.g., Zwingmann et al, 2014), future research is strongly needed that replicates our findings across various countries to determine their reach. In a similar way, as mean levels of OTE have been shown to vary across countries and as it has been argued that OTE has a different function in collectivist nations (Hofstede, 2001;Schmitt et al, 2007), it would be worthwhile to investigate the effect of OTE on the TFL-burnout link in various countries.…”
Section: Suggestions For Future Researchmentioning
confidence: 80%
“…Lastly, as research that examined TFL across multiple countries found that cultural dimensions influence its effects (e.g., Zwingmann et al, 2014), future research is strongly needed that replicates our findings across various countries to determine their reach. In a similar way, as mean levels of OTE have been shown to vary across countries and as it has been argued that OTE has a different function in collectivist nations (Hofstede, 2001;Schmitt et al, 2007), it would be worthwhile to investigate the effect of OTE on the TFL-burnout link in various countries.…”
Section: Suggestions For Future Researchmentioning
confidence: 80%
“…Third, to present new instruments and measures to assess and understand health-promoting leadership at work (Franke et al, 2014;Stocker, Jabobshagen, Krings, Pfister, & Semmer, 2014). Fourth, to explore the antecedents and moderators of health-promoting leadership across different levels of an organization and across different cultures (Steffens, Haslam, Kerschreiter, Schuh, & van Dick, 2014;Zwingmann et al, 2014). Fifth, to clarify the role of empowerment and task demands of employees in this process (Walsh et al, 2014;Franke et al, 2014) and also explore the health of leaders as an antecedent of health-promoting leadership and potential spillover processes (Franke et al, 2014).…”
Section: Leader Behavior As a Determinant Of Health At Work: Specificmentioning
confidence: 99%
“…First, to understand how and why leadership behavior in organizations promotes (or else harms) the health of employees (Franke, Felfe, & Pundt, 2014;Gregersen, Vincent-Höper, & Nienhaus, 2014;Winkler, Busch, Clasen, & Fohwinkel, 2014;Walsh, Dupré, & Arnold, 2014;Rivkin, Diestel, & Schmidt, 2014). Second, to elucidate potential differences between leadership approaches in explaining health at work (Gregersen et al, 2014;Franke et al, 2014;Zwingmann, Wegge, Wolf, Rudolf, Schmidt, & Richter, 2014). Third, to present new instruments and measures to assess and understand health-promoting leadership at work (Franke et al, 2014;Stocker, Jabobshagen, Krings, Pfister, & Semmer, 2014).…”
Section: Leader Behavior As a Determinant Of Health At Work: Specificmentioning
confidence: 99%
“…Another research indicated that transformational leadership and contingent reward supported health promotion among subordinates [6]. Employees led by such superiors reported better health and such result could be observed among employees from all 16 studied countries.…”
mentioning
confidence: 69%
“…The extant literature suggests that managers' leadership skills and behavior influence their subordinates' well-being or health through their impact on creating working conditions and the possibility to provide their subordinates with health-promoting resources [5,6,9]. However, many organizations seem to neglect the contribution of the managers to employees' stress, and stress-related illnesses [1].…”
Section: Discussionmentioning
confidence: 99%